BRAINSTORMING TECHNIQUE IS TO IMPROVE STUDENTS’ SPEAKING ABILITY - zainuddin zainuddin (JURNAL LINER (Language Intelligence and Educational Research), 2022)
The discussion is about brainstorming technique is to improve students’ speaking ability. It is done at grade XI MAN Siabu. There were reasons to do the research such as Most of students couldn’t speak English well, Students were afraid and feeling ashamed to speak English and English Teacher didn’t use speaking technique in learning speaking subject. Based on the general problem above the formulation in this research was “to what extent brainstorming technique can improve students’ speaking ability at grade XI MAN Siabu?“. This research aimed to know whether Brainstorming Technique can improve students’ speaking ability or not. Moreover, this research was done by using classroom action research by using brainstorming technique to improve students’ speaking ability. The action in this research was done into two cycles. Each cycle consisted of two meetings with four steps. They were planning, action, observation and reflection. The subject was the grade XI MAN SIABU that consisted of 30 students. Here, the researcher used test, observation and interview for the instruments of the research. Finally, the researcher found meant score 57.6. For the first cycle students’ speaking ability. It was an indication that students were low in speaking ability. Whereas meant score79.5. was taken for second cycle of students’ speaking ability improvement. It then there was an indication of students’ speaking ability improvement. So, based on the result of the classroom action research, it was concluded that the brainstorming technique improved students’ speaking ability in MAN SIABU. It was all viewed on the meant scores of students’ speaking ability like in cycle 1 was 57.6 and in cycle 2 was 79.5. Keywords: Technique, brainstorming, cycle